IFPRI Nexus SAMs: Annual Release Note 2024 - Randriamamonjy, Josee; Jones, Eleanor; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2024)
The Nexus Project is pleased to provide an update on the Nexus Social Accounting Matrices (SAMs) developed and released by IFPRI in collaboration with national statistical agencies and research institutions in 2024. This Annual Release Note provides a brief overview of SAMs and the Nexus Project. It serves as a useful one-stop shop for obtaining links to the latest versions of all Nexus SAMs. For more information or questions, please email IFPRI-Nexus@cgiar.org.